2019
DOI: 10.3390/molecules24040711
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Ultrasound-Assisted Extraction Condition for Flavonoid Compounds from Cocoa Shells (Theobroma cacao) Using Response Surface Methodology

Abstract: This study investigates the ultrasound-assisted extraction of flavonoids from Malaysian cocoa shell extracts, and optimization using response surface methodology. There are three variables involved in this study, namely: ethanol concentration (70–90 v/v %), temperature (45–65 °C), and ultrasound irradiation time (30–60 min). All of the data were collected and analyzed for variance (ANOVA). The coefficient of determination (R2) and the model was significant in interaction between all variables (98% and p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 54 publications
5
27
0
3
Order By: Relevance
“…When a maximum TFC was obtained, a further increase in ethanol concentration induced a decrease in the TFC, which is consistent with the result of the flavonoids extraction from cocoa shells [31], Dendrobium officinale [32], and Bombyx batryticatus [7]. Studies have shown that ethanol concentration is one of the most important factors affecting the extraction of flavonoids [7,31,32]. Changing the ethanol concentration adjusts the polarity of the extraction solvent and alters the solubility of flavonoids, thus affecting the efficiency of the flavonoids extraction [32].…”
Section: Mutual Effect Of Extraction Factorssupporting
confidence: 88%
See 4 more Smart Citations
“…When a maximum TFC was obtained, a further increase in ethanol concentration induced a decrease in the TFC, which is consistent with the result of the flavonoids extraction from cocoa shells [31], Dendrobium officinale [32], and Bombyx batryticatus [7]. Studies have shown that ethanol concentration is one of the most important factors affecting the extraction of flavonoids [7,31,32]. Changing the ethanol concentration adjusts the polarity of the extraction solvent and alters the solubility of flavonoids, thus affecting the efficiency of the flavonoids extraction [32].…”
Section: Mutual Effect Of Extraction Factorssupporting
confidence: 88%
“…is result is consistent with the ultrasound-assisted extraction of flavonoids from olive leaves [16] and cocoa shells [31], polysaccharides extraction from A. selengensis [21], and the ultrasound-assisted extraction of phenolic from Trapa quadrispinosa [15].…”
Section: Mutual Effect Of Extraction Factorssupporting
confidence: 86%
See 3 more Smart Citations